2020
DOI: 10.1002/jbm.a.36893
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and toxicity of epitope‐functionalized dextran iron oxide nanoparticles in a pregnant murine model

Abstract: In pursuit of a preventive therapeutic for maternal autoantibody‐related (MAR) autism, we assessed the toxicity, biodistribution, and clearance of a MAR specific peptide‐functionalized dextran iron oxide nanoparticle system in pregnant murine dams. We previously synthesized ~15 nm citrate‐coated dextran iron oxide nanoparticles (DIONPs), surface‐modified with polyethylene glycol and MAR peptides to produce systems for nanoparticle‐based autoantibody reception and entrapments (SNAREs). First, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Toxicokinetic analysis showed that IONPs exhibited an appropriate elimination rate and a favorable dose-response relationship in the blood after intravenous administration. The tissue distribution results indicated that IONPs were delivered to a range of organ systems after entering the systemic circulation, in accordance with the results from numerous studies (Yu et al, 2018;Gaharwar et al, 2019;Bolandparvaz et al, 2020). In the present study, the highest IONPs deposition in the spleen and liver indicated that these two organs played the most important role in IONPs elimination from the systemic circulation.…”
Section: Discussionsupporting
confidence: 91%
“…Toxicokinetic analysis showed that IONPs exhibited an appropriate elimination rate and a favorable dose-response relationship in the blood after intravenous administration. The tissue distribution results indicated that IONPs were delivered to a range of organ systems after entering the systemic circulation, in accordance with the results from numerous studies (Yu et al, 2018;Gaharwar et al, 2019;Bolandparvaz et al, 2020). In the present study, the highest IONPs deposition in the spleen and liver indicated that these two organs played the most important role in IONPs elimination from the systemic circulation.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, aspects related to the biodistribution of iron oxide nanoparticles coated with different materials have been studied recently [ 34 , 35 , 36 , 37 , 38 , 39 ]. In their study regarding the “Genotoxicity and biocompatibility of superparamagnetic iron oxide nanoparticles: influence of surface modification on biodistribution, retention, DNA damage and oxidative stress”, Gosh et al [ 34 ] reported the use of poly (lactic-co-glycolic acid) together with either didodeclydimethyl-ammonium-bromide or α-tocopheryl-polyethleneglycol-succinate in order to reduce the cytogenotoxicity and the generation of reactive oxygen species of iron oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…These complex interactions between the biological milieu and the nanoparticle depend on multiple factors such as synthetic identity, the biological microenvironment, and the interaction time with the organism. The possibility of functionalizing IONPs with biomolecules such as peptides [ 14 , 15 ], ligands [ 16 ], antibodies [ 17 , 18 ], aptamers [ 19 , 20 ], or RNAs [ 21 ] further enables IONPs to interact with a specific cell type or tissue; for instance, antibody-functionalized IONPs can specifically target antigen-expressing tumor cells, which allows local application of an alternative magnetic field for the induction of magnetic hyperthermia [ 22 ]. Understanding these interactions and how they influence the intended application of the synthesized nanoparticle is critical, as such knowledge not only allows for more rational nanomaterial design but could also enable these previously undiscovered characteristics to be harnessed for combinatorial therapies.…”
Section: Introductionmentioning
confidence: 99%